PENGARUH ATHLETE ENDORSEMENT, PERSEPSI HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SEPATU AZA DIMODERASI SPORT INVOLVEMENT HALAMAN SAMPUL - Arief Dwi Wicaksono; Wijayanto, Andi; Dewi, Reni Shinta (Modus, 2023)
The purpose of this study is to determine the effects of athlete endorsement, price perception, and product quality on local basketball shoe purchasing decisions, and the influence of sport involvement moderating athlete endorsement, price perception, and product quality on purchasing decisions of local AZA brand basketball shoes. This research is explanatory research using purposive sampling followed by snowball sampling. The total sample obtained was 100 respondents. Data analysis technique used was MRA. The results found are: 1) there is an influence of athlete endorsement on the purchasing decision of local basketball shoes; 2) there is an influence of price perception on the purchasing decision of local basketball shoes; 3) there is an effect of product quality on purchasing decisions for local basketball shoes, and; 4) there is an influence of sport involvement moderating athlete endorsement, price perception, and product quality on purchasing decisions for local basketball shoes brand AZA. Keywords: athlete endorsement; sport involvement; local shoes. Penelitian ini bertujuan untuk mengetahui pengaruh athlete endorsement, persepsi harga, dan kualitas produk terhadap keputusan pembelian sepatu basket lokal, serta pengaruh sport involvement memoderasi athlete endorsement, persepsi harga, dan kualitas produk terhadap keputusan pembelian sepatu basket lokal merek AZA. Penelitian ini termasuk dalam penelitian eksplanatori dengan teknik sampling penelitian ini adalah purposive sampling dilanjutkan dengan snowball sampling. Sampel didapatkan 100 responden. Teknik analisis data menggunakan MRA. Hasil yang ditemukan yaitu: 1) terdapat pengaruh athlete endorsement terhadap keputusan pembelian sepatu basket lokal; 2) terdapat pengaruh persepsi harga terhadap keputusan pembelian sepatu basket lokal; 3) terdapat pengaruh kualitas produk pada keputusan pembelian sepatu basket lokal, dan; 4) terdapat pengaruh sport involvement memoderasi athlete endorsement, persepsi harga, dan kualitas produk terhadap keputusan pembelian sepatu basket lokal merek AZA. Kata kunci: athlete endorsement; sport involvement; sepatu lokal.